Desenvolvimento de protocolo clínico para detecção precoce de lesões precursoras do câncer de colo uterino - Sousa, Deise Maria do Nascimento (2015)
This study develops and validates the content of a clinical protocol directed to gynecological nursing consultating for prevention of cervical cancer in primary care. This was a technological research. To conduct the study, we used the following steps: (1) submission of the project to the ethics committee in research; (2) bibliographical research; (3) preparation of the clinical protocol and (4) validation of the material by expert judges. The texts for step 3 were drawn from information gathered in step 2 and consulted gynecology specialists. Four judges were selected according to pre-established criteria to validate content, according to pre-established criteria. The data collection period with judges occurred between May and June 2015. For data collection, an instrument directed to the judges it was used. For the validity of content by the judges, it was considered validated domains those that obtained a minimum level of agreement of 75% in scores. The suggestions and opinions were presented descriptively. The clinical protocol for the study validated the material, since the score obtained in each mastery of the instrument are as follows: Domain 1 (scope and purpose) = 87.5%; Domain 2 (stakeholder engagement) - 83.3%; Domain 3 (development rigor) = 79.7%; the domain 4 (clarity of presentation) = 76.3%; the domain 5 (obligatory) = 78.1% and area 6 (editorial independence) = 85.4. The clinical protocol received positive recommendations with modifications. On the suggestions and contributions during the validation process, the clinical protocol underwent modifications, adjustments and additions to make it more effective. It is believed that the use of this material in health care gynecology would facilitate the practice of nursing, considering that it constitutes a technology to improve the tracking of cervical cancer.